64 Cu Treatment Planning and 67 Cu Therapy with Radiolabeled [ 64 Cu/ 67 Cu]MeCOSar-Octreotate in Subjects with Unresectable Multifocal Meningioma: Initial Results for Human Imaging, Safety, Biodistribution, and Radiation Dosimetry - Bailey, Dale L.; Willowson, Kathy P.; Harris, Matthew; Biggin, Colin; Aslani, Alireza; Lengkeek, Nigel A.; Stoner, Jon; Eslick, M. Enid; Marquis, Harry; Parker, Michelle; Roach, Paul J.; Schembri, Geoffrey P. (Journal of Nuclear Medicine, 2023)
Our aim was to report the use of Cu and Cu as a theranostic pair of radionuclides in human subjects. An additional aim was to measure whole-organ dosimetry of Cu and Cu attached to the somatostatin analog octreotate using the sarcophagine MeCOSar chelator (SARTATE) in subjects with somatostatin receptor-expressing lesions confined to the cranium, thereby permitting normal-organ dosimetry for the remainder of the body. Pretreatment PET imaging studies were performed up to 24 h after injection of [ Cu]Cu-SARTATE, and normal-organ dosimetry was estimated using OLINDA/EXM. Subsequently, the trial subjects with multifocal meningiomas were given therapeutic doses of [ Cu]Cu-SARTATE and imaged over several days using SPECT/CT. Five subjects were initially recruited and imaged using PET/CT before treatment. Three of the subjects were subsequently administered 4 cycles each of [ Cu]Cu-SARTATE followed by multiple SPECT/CT imaging time points. No serious adverse events were observed, and no adverse events led to withdrawal from the study or discontinuation from treatment. The estimated mean effective dose was 3.95 × 10 mSv/MBq for [ Cu]Cu-SARTATE and 7.62 × 10 mSv/MBq for [ Cu]Cu-SARTATE. The highest estimated organ dose was in spleen, followed by kidneys, liver, adrenals, and small intestine. The matched pairing was shown by PET and SPECT intrasubject imaging to have nearly identical targeting to tumors for guiding therapy, demonstrating a potentially accurate and precise theranostic product. Cu and Cu show great promise as a theranostic pair of radionuclides. Further clinical studies will be required to examine the therapeutic dose required for [ Cu]Cu-SARTATE for various indications. In addition, the ability to use predictive Cu-based dosimetry for treatment planning with Cu should be further explored.